2010
DOI: 10.1093/eurheartj/ehq381
|View full text |Cite
|
Sign up to set email alerts
|

Risk stratification in individuals with the Brugada type 1 ECG pattern without previous cardiac arrest: usefulness of a combined clinical and electrophysiologic approach

Abstract: AimsRisk stratification in individuals with type 1 Brugada electrocardiogram (ECG) pattern (type 1 ECG) for primary prevention of sudden death (SD).Methods and resultsThree hundred and twenty patients (258 males, median age 43 years) with type 1 ECG were enrolled. No patient had previous cardiac arrest. Fifty-four per cent of patients had a spontaneous and 46% a drug-induced type 1 ECG. One-third had syncope, two-thirds were asymptomatic. Two hundred and forty-five patients underwent electrophysiologic study (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
142
2
7

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 197 publications
(152 citation statements)
references
References 25 publications
1
142
2
7
Order By: Relevance
“…21 Delise et al, however, reported that no arrhythmic events occurred in patients with negative inducibility of VF. 10 Makimoto et al reported that the number of extrastimuli in PES using the minimum coupling interval of 180 ms and the inducibility of VF by up to 2 extrastimuli had significant predictive value for future cardiac events. 22 Further discussion of these unresolved issues should be continued.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21 Delise et al, however, reported that no arrhythmic events occurred in patients with negative inducibility of VF. 10 Makimoto et al reported that the number of extrastimuli in PES using the minimum coupling interval of 180 ms and the inducibility of VF by up to 2 extrastimuli had significant predictive value for future cardiac events. 22 Further discussion of these unresolved issues should be continued.…”
Section: Discussionmentioning
confidence: 99%
“…Delise et al reported the risk stratification in a similar patient type as in the present study, with a focus on risk combinations. 10 Although FH itself failed to predict arrhythmic events, the authors concluded that a multi-parametric approach that included syncope, FH, and PES+ helped to identify patients at high risk. They also reported that the patients at highest risk were those with at least 2 risk factors in addition to Sp1.…”
Section: Combining Risk Factors For Vfmentioning
confidence: 99%
“…Risk stratification in BS is still controversial. Implantable cardioverter-defibrillators (ICDs) are inserted to the patients experienced cardiac arrest, syncope and whose ECG showed type I pattern, inducible ventricular arrhythmia with programmed ventricular stimulation (3). A report by Raju et al (4) demonstrated that the majority of individuals experiencing BS sudden death are asymptomatic before their terminal event and 68% of surviving patients has no ICD indication according to current guidelines.…”
mentioning
confidence: 99%
“…Third, of the 18 identified studies, only 8 participated and 84% of the study population was pooled from 3 studies. [9][10][11] Fourth, the included studies have little contribution from the high-risk Asian population, and none are authored by one of the Brugada brothers. It is well recognized that their experience strongly endorses risk stratification with PES.…”
Section: Article See P 622mentioning
confidence: 99%
“…2 This unique interaction between channelopathy and substrate may, in part, explain the inconsistent findings reported with PES. Considering conflicting literature, [3][4][5][6][7][8][9][10][11] consensus statements suggesting a lesser role, 14 and statistical analysis of the current publication, if and how PES should be incorporated into the algorithm for managing BrS remains unsettled.…”
Section: Article See P 622mentioning
confidence: 99%